Evidence and Innovation in Housing Law and Policy - Anne Fennell, Lee; Keys, Benjamin J. (Social Sciences, 2017)
These accessible, interdisciplinary contributions show how housing law and policy impacts household wealth, financial markets, urban landscapes, and local communities. A key resource for academics, students, policymakers, and laypeople interested in housing issues. This title is also available as Open Access.